Steganography Technique to Hide a Secret Message in QR Code (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This paper proposes a new method to hide a message in Quick Response code (QR code). This type of image steganography is quite a challenge because the secrete message should not be detected by the standard QR code reader. In addition, it has to be stored in an appropriate location that does not affect the original data of the QR code. All these requirements are studied. The analysis method is presented and discussed.